Pancreatic solid pseudopapillary neoplasm: clinical, computed tomography and endoscopic ultrasound features unraveling a rare tumor with pathologic correlation - Fatmaelzahraa Abdelfattah Denewar; Ahmed E. Eladl; Fatma Mohamed Sherif; Omar Abdallah; Elsayed Ghoneem; Khadija Denewar; Eman Fouad Omran; Zainab A. Ramadan (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Solid pseudopapillary neoplasm (SPN) of the pancreas exhibits low malignant potential and is typically curable via surgical excision, with > 90% 5-year survival rates, including metastatic cases. Accurate preoperative diagnosis is crucial to minimize surgical extent. We aimed to elucidate distinctive imaging features of SPN on computed tomography (CT) and endoscopic ultrasound (EUS) with pathologic correlation, enabling radiologists to better recognize and distinguish them from other pancreatic lesions. Methods Thirty three patients (3 men, and 30 women; median age of 25 years) with pathologic diagnosis of SPN encountered between November 2019 and July 2024 were included in this study. CT images with pancreatic triphasic protocol were reviewed for tumor location, size, shape, margin, morphology, presence of capsule, calcification, hemorrhage, invasion, enlarged lymph nodes, and bile duct dilatation. Enhancement pattern was assessed and CT attenuation values were calculated. EUS was conducted in 15 patients and its sensitivity in diagnosing SPN was compared to CT alone. Results Most patients in our series were symptomatic young females. Dominant CT features included a well-defined encapsulated lesion with mixed solid/cystic appearance, variable degrees of hemorrhage and calcifications, heterogeneous hypo-enhancement during arterial phase with peak enhancement in portal venous phase, non-dilated bile duct, and absence of liver metastasis. Combining CT and EUS in 15 patients enhanced diagnostic sensitivity compared to CT alone. Conclusion A mixed solid/cystic pancreatic mass in a young woman with progressive enhancement and variable degrees of hemorrhage and calcifications is suggestive of SPN. Combining CT and EUS could enhance preoperative diagnostic accuracy. Despite being a descriptive study with limited scope, this institutional case series provides descriptive insights into tumor characteristics, aligning with existing literature and expanding the collective knowledge base.